Pyoderma gangrenosum in primary care setting: the challenges involved - Beenish Fayyaz (Greater Baltimore Medical Center, 2018)
This article aims at raising clinical awareness about pyoderma gangrenosum especially when presenting in primary care settings. Due to its initial manifestation as a nonspecific ulcer, physicians with relatively less dermatology experience usually misdiagnose PG as cutaneous infection or vascular disease. This usually leads to inappropriate treatment with subsequent worsening of condition and devastating effects on patients' lives.